PENGGUNAAN GAYA BAHASA PADA TOKOH DALAM FILM “MENCURI RADEN SALEH” - Novera, Elsa Siti; Putriana, Ines Indriani; Nurjanah, Laila Fitri (Institut Seni Budaya Indonesia Bandung, 2023)
ABSTRACT This research contains an analysis of the use of language styles of the characters in the film